2010
DOI: 10.1007/s00441-010-1064-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human full-length amelogenin on the proliferation of human mesenchymal stem cells derived from bone marrow

Abstract: Amelogenins are enamel matrix proteins that play a crucial role in enamel formation. Recent studies have revealed that amelogenins also have cell signaling properties. Although amelogenins had been described as specific products of ameloblasts, recent research has demonstrated their expression in bone marrow stromal cells. In this study, we examined the effect of recombinant human full-length amelogenin (rh174) on the proliferation of human mesenchymal stem cells (MSCs) derived from bone marrow and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Disturbed EMP expression patterns are associated with alveolar and jaw bone malformations [33], [34]. These findings and the present data suggest that solubilized EMPs may play a role in controlling cell fate through short-distance paracrine and autocrine functions and thus control local bone morphology via signals previously evidenced for AMBN [19], [53], [54] and AMELX [55], [56]. We thus propose a model in which EMPs play a role in mandibular physiology (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Disturbed EMP expression patterns are associated with alveolar and jaw bone malformations [33], [34]. These findings and the present data suggest that solubilized EMPs may play a role in controlling cell fate through short-distance paracrine and autocrine functions and thus control local bone morphology via signals previously evidenced for AMBN [19], [53], [54] and AMELX [55], [56]. We thus propose a model in which EMPs play a role in mandibular physiology (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Together, these findings illustrate that both Amel and Ambn ERPs exhibit highly visible effects on bone matrix mineralization and bone marker gene expression. The concept that ERPs are involved in osteoblast differentiation or bone matrix mineralization is supported by several previous studies related to the role of Amel in the modulation of mineralized tissue homeostasis, including activation of osteoclastogenesis (Hatakeyama et al, 2006), modulation of cementogenesis (Swanson et al, 2006), and bone marrow stem cell proliferation (Huang et al, 2010). Recent studies suggested that Ambn binds CD63 and may act through integrin β1 and C Src kinase inhibition to promote osteogenic differentiation (Iizuka et al, 2011;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 84%
“…It has been suggested that EMD and the other amelogenin peptides can regulate cellular functions through the ERK 1/2 signaling pathway [41,42]. We speculated that cell proliferation and osteoblastic differentiation of human MSCs are regulated by the ERK 1/2 signaling pathway as well as EMD.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, using the ERK 1/2 inhibitor, PD98059, we examined the molecular mechanism by which SP affects cell proliferation and osteoblastic differentiation in human MSCs. The concentration of the inhibitor (10 µM) was set according to a previous report [41]. As shown in Figure 5, Figure 6, Figure 7 and Figure 8, the inhibitor significantly suppressed cell proliferation and osteoblastic differentiation induced by SP.…”
Section: Resultsmentioning
confidence: 99%